1994
DOI: 10.3347/kjp.1994.32.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Status of parasitic infection diagnosed by surgical biopsy in Kwangju and Chollanam-do

Abstract: In order to know the species and frequency of human parasitic infection diagnosed by biopsy, 149 cases (0.18%) of parasitic infection were reviewed, which were selected from 80,947 biopsied materials submitted for routine histopathological examination during a period of 10 years from 1980 to 1989 at Department of Pathology, Chonnam National University Hospital. They consisted of 112 cases of cysticercosis, 17 paragonimiasis, 7 clonorchiasis, 4 amebiasis, 1 sparganosis, 1 enterobiasis, 1 anisakiasis, and 1 fasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Superoxide radical generated from molecular oxygen via an electron transfer step which causes DNA cleavage by guanine oxidation, in case of nickel(II) complex singlet oxygen only modifies the guanine residues. The singlet oxygen might form as a result of hydrogen peroxide reacting 41,42 with O 2 coordinated with Ni atom in the complex. The significant increase in the DNA cleavage activity by 1 in the presence of H 2 O 2 and the inhibition of activity in the presence of DMSO, KI, NaN 3 and EDTA suggest that this reaction was preferentially proceeded by a hydroxyl radical mechanism with •OH and NT-Not tested singlet oxygen species.…”
mentioning
confidence: 99%
“…Superoxide radical generated from molecular oxygen via an electron transfer step which causes DNA cleavage by guanine oxidation, in case of nickel(II) complex singlet oxygen only modifies the guanine residues. The singlet oxygen might form as a result of hydrogen peroxide reacting 41,42 with O 2 coordinated with Ni atom in the complex. The significant increase in the DNA cleavage activity by 1 in the presence of H 2 O 2 and the inhibition of activity in the presence of DMSO, KI, NaN 3 and EDTA suggest that this reaction was preferentially proceeded by a hydroxyl radical mechanism with •OH and NT-Not tested singlet oxygen species.…”
mentioning
confidence: 99%
“…Similarly, in 1972-1983, 136 (0.30%) cysticercosis cases were detected out of a total of 45,651 surgical biopsies examined in the Department of Pathology, Kyunghee University Medical Center in Seoul [57]. Another study during 1980-1989 found 112 (0.14%) cysticercosis cases out of a total of 80,947 biopsies in the Department of Pathology, Chonnam National University Hospital [58]. However, this ratio became much lower in a follow-up study (1984-2005) in Kyunghee University Medical Center; only 62 (0.029%) were found to be cysticercosis out of a total of 211,859 surgical biopsies [59], which is only 1/5-1/15 that of previous reports [56-58].…”
Section: Decrease Of Human Cysticercosismentioning
confidence: 99%
“…Another study during 1980-1989 found 112 (0.14%) cysticercosis cases out of a total of 80,947 biopsies in the Department of Pathology, Chonnam National University Hospital [58]. However, this ratio became much lower in a follow-up study (1984-2005) in Kyunghee University Medical Center; only 62 (0.029%) were found to be cysticercosis out of a total of 211,859 surgical biopsies [59], which is only 1/5-1/15 that of previous reports [56-58]. These trends of the decrease of cysticercosis among the toal biopsy cases, in particular, data derived from Seoul National University Hospital (1968-1987) [56] and Kyunghee University Medical Center (1972-2005) [57,59] are depicted in Fig.…”
Section: Decrease Of Human Cysticercosismentioning
confidence: 99%
“…Another study of surgical specimens revealed that 149 of 80,947 cases (0.18%) were of parasitic origin. Of these, 112 cases were cysticercosis involving several organs, most commonly subcutaneous tissues and muscles [8]. From 1993 to 2006, a total of 74,448 serum samples obtained from patients with neurological manifestations and liver diseases were tested by ELISA.…”
Section: Introductionmentioning
confidence: 99%